Integration of ICT in Teaching and Learning, Teachers Motivation and Skills of Teaching Literature: A Structural Model Equation on Academic Performance - Elmer A. Taripe; Marilou Limpot (Archives of Current Research International, 2022)
Aims: To investigate the most appropriate model in academic performance using structural equation modeling (SEM) as the basis for the tool’s design to analyze the relationship between the integration of ICT in learning and teaching, teacher motivation, and skills in teaching literature. Study Design: Descriptive-causal design. Place and Duration of Study: The study was conducted among 400 college students from both public and private academic institutions in Regions 11 and 13 during the school year 2021-2022. Methodology: The respondents were selected using stratified random sampling. Mean, standard deviation, Pearson product-moment correlation, and multiple regression analysis were used to analyze the collected data. Results: Results revealed that the ICT integration in learning and teaching, teacher motivation, and literature teaching skills had the highest means while academic performance was high. The integration of ICT in learning and teaching, teacher motivation, and literature teaching skills had a significant relationship with academic performance. The most appropriate model for academic performance was model 5, with indicators of personal status, study habits, home-related factors, school-related factors, and teacher-related factors. Conclusion: The result proved that the knowledge of the integration of ICT in teaching and learning, teacher motivation, and teacher skill in teaching literature are predictors of academic performance.